A techno-economic perspective on solar-to-hydrogen concepts through 2025. Issue 11 (9th October 2020) - Grube, Thomas; Reul, Julian; Reuß, Markus; Calnan, Sonya; Monnerie, Nathalie; Schlatmann, Rutger; Sattler, Christian; Robinius, Martin; Stolten, Detlef
Abstract : With this comparative study, we present an advanced approach to the techno-economic assessment of solar-based hydrogen production. Abstract : The transition towards a renewable energy-based society is challenged by spatial and temporal imbalances of energy demand and supply. Storage properties and versatility may favor hydrogen to serve as the linking element between renewable energy generation and a variety of sector coupling options. This paper examines four alternative solar-based hydrogen production concepts based on concentrated solar (CSP) or photovoltaic (PV) power generation and solid oxide (SOE) or polymer electrolyte membrane (PEM) electrolysis, namely, CSP-SOE and CSP-PEM, as well as PV-PEM concepts with (PV-PEM I) or without (PV-PEM II) power converters coupling both devices. In this paper, we analyze these concepts in terms of their techno-economic performance in order to determine the levelized cost of hydrogen (LCOH) for the target year 2025, based on different locations with different climate conditions. The analysis was carried out using a broadly applicable computer model based on an hourly resolved time-series of temperature and irradiance. The lowest LCOH was identified in the case of the CSP-SOE and CSP-PEM concepts with 14–17 €-ct per kW per h at high-irradiance locations, which clearly exceed the US Department of Energy (DOE) target of 6 $-ct per kW per h for the year 2020. Moreover, CSP-SOE also shows the highest hydrogen production volumes and, therefore, solar-to-hydrogen efficiencies. Considering the PV-PEM concepts, we found that the application of power converters for the electrical coupling of PV modules and electrolyzers does not contribute to cost reduction due to the higher related investment costs. A further system optimization is suggested regarding the implementation of short-term energy storage, which might be particularly relevant at locations with higher fluctuations in power supply.